Globalization and military-industrial transformation in South Asia: An historical perspective - Chew, Emrys (2016)
This paper attempts to demonstrate the relevance of the historical method and the importance of identifying long-term globalizing patterns in understanding the military-industrial transformation and militarization of South Asia. Out of this particular historical matrix would flow the events of 9/11, as well as ongoing developments in the global ‘war on terror’, fought out in the wider periphery of South Asia. Across a levelled and shell-shocked post-9/11 landscape, it has become even more important to apply this vital long-term perspective to our understanding of the present, so as to avoid the twin pitfalls of myopia and amnesia: viewing the ‘modern’ phenomenon of South Asia’s militarization in deracinated form, and thereby failing to recall the broader connections and long-term patterns; or, at best, giving only cursory attention thereto. What is new today, on the other hand, is the raising of stakes in a world of nation-states having volatile nuclear capabilities and rapid internet communication; and, in the midst of pre-existing indigenous rivalries, the capacity of local warlords, resistance fighters or jihadists to re-export ‘terror’ as far afield as the core of the Western metropole. The paper examines the roots and ramifications of military-industrial globalization in South Asia, locating them firmly within the dynamic military cultural context of the subcontinent’s history. In so doing, it strives to redress perceived imbalances in the contemporary emphasis of current debates about the nature and impact of globalizing supra-national forces. It also seeks to review possible implications of long-term trends and patterns for the future security of the region.